2007
DOI: 10.1037/1064-1297.15.1.81
|View full text |Cite
|
Sign up to set email alerts
|

High-dose transdermal nicotine and naltrexone: Effects on nicotine withdrawal, urges, smoking, and effects of smoking.

Abstract: Although treatment with transdermal nicotine replacement (TNR) has improved smoking abstinence rates, higher doses of TNR could improve effects on urge to smoke, nicotine withdrawal, and reinforcement from smoking, and naltrexone might further reduce reinforcement and urges. A laboratory investigation with 134 smokers using a 3 x 2 parallel-group design evaluated the effects of TNR (42-mg, 21-mg, or 0-mg patch) as crossed with a single dose of naltrexone (50 mg) versus placebo on urge to smoke, withdrawal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
6
34
0
Order By: Relevance
“…This finding is consistent with some other studies (e.g., Rohsenow et al, 2007;Tidey et al, 2005). A methodological concern that has been raised about smoking cuereactivity paradigms is that smoking deprivation alone may raise craving to levels where the cue-reactivity effects are no longer noticeable due to ceiling effects, possibly explaining why weaker reactivity effects have been observed when participants are nicotine deprived as compared to non-deprived (e.g., Sayette et al, 2001;Tidey et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is consistent with some other studies (e.g., Rohsenow et al, 2007;Tidey et al, 2005). A methodological concern that has been raised about smoking cuereactivity paradigms is that smoking deprivation alone may raise craving to levels where the cue-reactivity effects are no longer noticeable due to ceiling effects, possibly explaining why weaker reactivity effects have been observed when participants are nicotine deprived as compared to non-deprived (e.g., Sayette et al, 2001;Tidey et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Second, this study compared participants' reactivity to smoking cues with their responses following a relaxation period rather than with their responses to a neutral cue condition; although our previous work indicated that this approach should make no difference (Rohsenow et al, 2007), this methodology should be taken into consideration when generalizing these findings to other cue reactivity studies. In addition, while caffeine has known effects on physiological reactivity (but not on urge to smoke or withdrawal measures), participants were not asked to abstain from caffeine prior to the laboratory session and recent caffeine consumption was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual-controller account elaborated above provides a framework for explaining why tonic cigarette craving but not cue-elicited craving is modulated by abstinence/satiety (Drobes & Tiffany, 1997;Hogarth, et al, 2010;Maude-Griffin & Tiffany, 1996) nicotine replacement therapy (Havermans, et al, 2003;Morissette, et al, 2005;Niaura, et al, 2005;Rohsenow, et al, 2007;Shiffman, et al, 2003;Tiffany, et al, 2000;Waters, et al, 2004), bupropion (Hussain, et al, 2010) and varenicline (Brandon, et al, 2011;Franklin, et al, 2011;Hitsman, et al, under review;Hitsman, et al, 2006). The current analysis suggests that these treatments induce or mimic internal states which have undergone incentive learning and so modulate expectations regarding the current incentive value of tobacco, which determines overall propensity to engage in goal-directed tobacco-seeking (tonic craving).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Future research examining gender differences in responses to smoking and stress cues should account for menstrual phase of female participants to maximize the chance of detecting effects that may be present. Another gainful line of future research could employ imaging methodologies to determine if stress cue-elicited neural activation differs between female and male smokers and if those differences vary by cycle phases (cf., Dagher et al 23 ).…”
Section: Discussionmentioning
confidence: 99%